Interaction Between Orexin‐A and Sleep Quality in Females in Extreme Weight Conditions. (November 2016) - Sauchelli, Sarah; Jiménez‐Murcia, Susana; Fernández‐García, Jose C.; Garrido‐Sánchez, Lourdes; Tinahones, Francisco J.; Casanueva, Felipe F.; Baños, Rosa M.; Botella, Cristina; Crujeiras, Ana B.; de la Torre, Rafael; Fernández‐Real, Jose M.; Frühbeck, Gema; et al.
Abstract: The current study examined the relationship between plasma orexin‐A and sleep in obesity. Concentrations of orexin‐A and sleep were evaluated in 26 obese, 40 morbid obese and 32 healthy‐weight participants. The sleep monitor Actiwatch AW7 and the Pittsburgh Sleep Quality Index were used to evaluate sleep. The Symptom Checklist‐90‐Revised was administered to assess symptoms of psychopathology. A higher weight status was associated with elevated orexin‐A levels ( p = .050), greater depression, anxiety and somatization symptoms (all: p < .001), and impoverished self‐reported sleep quality ( p < .001). A quadratic trend was found in objective sleep time, being longest in the obese group ( p = .031). Structural equation modelling showed plasma orexin‐A to be related to poor total sleep quality, which in turn was associated with elevated body mass index. Our data confirm an interaction between elevated plasma orexin‐A concentrations and poor sleep that contributes to fluctuations in body mass index. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.